Development and validation of the health belief model scale for early childhood caries prevention behaviors of parents - Ketian Wang; Gillian Hiu Man Lee; Pei Liu; Hey Ching Wong; Xiaoli Gao; Samuel Yeung Shan Wong; May Chun Mei Wong (BMC Oral Health)
Abstract Background Health Belief Model (HBM) is a theoretical model to assess perceptions about health behaviors. There is no comprehensive HBM scale to evaluate the early childhood caries (ECC) preventing behavior of parents. This study aimed to develop and validate a HBM scale to measure health beliefs concerning preventive behaviors for ECC. Specifically, the scale targeted parents with young children. Methods The initial item pool was set up by adapting existing HBM scales to assess parents’ health beliefs regarding their children’s ECC under six HBM domains and then underwent face and content validation. In the construct validation, parents were recruited and invited to complete the drafted HBM questionnaire, and the collected data were randomly divided into two equal halves. Explorative factor analysis (EFA) was performed to identify the latent constructs and items with factor loadings > 0.4 were extracted; Confirmative factor analysis (CFA) was conducted to crosscheck the constructs gained from EFA using each half of the data (n > 300). Model fit using the fit indices (GFI, CFI, and TLI, χ2/df, RMSEA) and reliability using Cronbach’s alpha were evaluated. Results In the drafted version, 27 items were formulated. Following face and content validation, a scale of 30 items under six HBM domains was created: perceived susceptibility (4 items), perceived severity (8 items), perceived benefits (4 items), perceived barriers (7 items), cue to action (4 items) and self-efficacy (3 items). A total of 628 questionnaires were completed and analyzed. Results from EFA showed that the 30 proposed items were loaded on six factors and accounted for 53.7% of the total variance. Twenty-five items with factor loadings ranging from 0.40 to 0.95 were loaded on their respective domains, three items were loaded on other domains. Two items had a factor loading lower than 0.4 and cross-loading was found on one item, which were omitted from further analysis. The 27 items were submitted to CFA, resulting in a final model of 25 items under six domains (GFI = 0.89, CFI = 0.94, TLI = 0.93, RMSEA = 0.054, χ2/df = 1.93). The reliability of the final model, as measured by Cronbach’s alpha, was 0.77. Conclusions This developed HBM scale demonstrated satisfactory reliability and validity, indicating its potential for measuring parents’ health beliefs regarding their children’s ECC prevention behaviors. Trial registration The data used in the present study was collected from the baseline survey of an RCT, which has been registered on Clinicaltrials.gov (NCT04665219). Registration date: 2020-12-04.